Sistem Analisis Tekstur Secara Statistik Orde Pertama Untuk Mengenali Jenis Telur Ayam Biasa Dan Telur Ayam Omega-3 - nurhayati, oky dwi (Jurnal Sistem Komputer, 2015)
Visually to distinguish ordinary chicken eggs and chicken eggs with omega-3 is very difficult because the physical shape and color of the eggs look the same. Â From the price, chicken eggs with omega-3 is more expensive than the ordinary eggs. This aim of the research is to create an analyst system which is able to recognize type of eggs based on the texture with several steps in image processing techniques. Several image processing techniques used namely conversion of the RGB image to gray scale, remove noise with a gaussian filter, segmentation using thresholding method, and analysis with first-order statistical method that are extracted from each image of eggs. Results of the research showed that the ordinary chicken eggs and chicken eggs with omega - 3 have different statistical values